Pimozide Inhibits Type II but Not Type I Hair Cells in Chicken Embryo and Adult Mouse Vestibular Organs - Roberta Giunta; Giulia Cheli; Giorgio Rispoli; Giancarlo Russo; Sergio Masetto (Biomedicines)
Background: Pimozide is a conventional antipsychotic drug of the diphenylbutylpiperidine class, widely used for treating schizophrenia and delusional disorders and for managing motor and phonic tics in Tourette’s syndrome. Pimozide is known to block dopaminergic D2 receptors and various types of voltage-gated ion channels. Among its side effects, dizziness and imbalance are the most frequently observed, which may imply an effect of the drug on the vestibular sensory receptors, the hair cells. Amniotes possess two classes of vestibular hair cells, named type I and type II hair cells, which differ in terms of signal processing and transmission. We previously reported that Pimozide [3 μM] significantly increased a delayed outward rectifying K+ current (IK,V). Methods and Results: In the present study, using the whole-cell patch-clamp technique we additionally show that Pimozide decreases the inward rectifying K+ current (IK,1) and the mixed Na+/K+ current (Ih) of chicken embryo type II hair cells, whereas it does not affect type I hair cells’ ionic currents. Since ion channels’ expression can vary depending on age and animal species, in the present study, we also tested Pimozide in adult mouse vestibular hair cells. We found that, like in the chicken embryo, Pimozide significantly increases IK,V and decreases IK,1 and Ih in type II hair cells. However, in the adult mouse, Pimozide also slightly increased the outward rectifying K+ current in type I hair cells. Conclusions: While providing a possible explanation for the vestibular side effects of Pimozide in humans, its inhibitory action on mammalian hair cells might be of interest for the local treatment of vestibular disorders characterized by altered vestibular input, like Ménière’s disease.